Profit Increase Efficiency Analysis; Production Approaches and Profit Approaches (Study on the Mining Sector in Indonesia) - Fadhilah (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2023)
Efficiency is the company's ability to maximize output by using certain inputs. This study aims to determine the level of efficiency and causes of inefficiency in mining sector companies listed on the IDX using the production approach and profit approach using quantitative Data Envelopment Analysis (DEA) methods and panel regression as measured using Eviews. The research object consists of 23 companies with data on the results of annual financial reports from 2017 to 2021. The test results show that there are differences in the results of company efficiency scores in the mining sector using the Production Approach and Profit approach. The results showed that from the production approach, only 2 companies were efficient and the remaining 21 companies were still experiencing inefficiencies from the results of cost of goods sold, selling expenses, operating expenses, and net sales which had a significant effect on efficiency, but total assets and general expenses & adm had no significant effect on efficiency. The results of the study using the profit approach were only 1 efficient company and the remaining 22 companies were still experiencing inefficiency, only total equity, selling expenses, and profit had a significant effect on efficiency, but the cost of sales, general & administrative expenses, operating expenses did not have a significant effect to be efficient. The number of companies that were not declared efficient in the year the company was researched had to do potential improvement by increasing assets, and equity, reducing the cost of goods sold, reducing selling expenses, general & administrative expenses, and operating expenses, and had to increase sales to increase profits and achieve efficiency in the company.